Exploring Internationalisation And Competitve Advantages Of SMEs : The Role Of Firm’s Network Capabity - Vinodbhai Udani, Amish (2021)
This study has examined the direct relationship of competitive advantages, management attitude, international experience & knowledge with internationalization; and direct relationship of internationalization with firm performance. Further, in this study we have examined moderating effect of network with internationalization and government initiatives with firm performance.